(x+2)(x-1)=2-3x
rearrange the formula into ax²+bx+c and use the quatradic equation to find x
Attachments:
![](https://hi-static.z-dn.net/files/da6/a20a35c1fd6e76cf98b696d875ad947e.jpg)
Answers
Answered by
0
Answer:
vco66756776⁶⁶⁶⁶⁶⁶⁶⁶⁶⁶6⁶⁶⁶⁶⁶6666
Answered by
0
Answer is
(X+2)(x-1)=2-3x
X^2-x+2x+3x=2+2
Therefore the answer is x^2-4x=4
So, x^2-4x-4
(X+2)(x-1)=2-3x
X^2-x+2x+3x=2+2
Therefore the answer is x^2-4x=4
So, x^2-4x-4
Attachments:
![](https://hi-static.z-dn.net/files/d9b/89b9353c92fe7b1c2aa0ffbcfba3efe6.png)
Similar questions